(untitled) (Journal of Bio-Science, 2018)
Sea cucumbers, marine animals from the class Holothuroidea, have been widely known as fishery products for consumption in Indonesia. The Madura Strait is productive waters for sea cucumbers in eastern Indonesia, including sea cucumber species Phyllophorus sp. The exploitation of it mainly for consumption even though there are pharmaceutical beneficial of sea cucumber already known. The study of temperature effect is ideal inducement method for sea cucumber, but less research about this stimulation for Phyllophorus sp. for domestication purposes. The research showed that thermal stimulation treatment at the temperature of 30°C, 32°C and 34°C were in contrast to the that of control histological analysis proof that some of Phyllophorus sp. showed altered levels of gonadal maturation toward growth and advanced growth phase after thermal stimulation, respectively. The ideal stimulation treatment for gonad maturation was shown with stimulated temperature treatment of 32°C. J. bio-sci. 23: 39-46, 2015